Les Lais de Marie au risque de l’amitié - Adélaïde Pilloux (Perspectives Médiévales)
Friendships between women have largely been made invisible, by medieval philosophy but also by modern and contemporary medievalist criticism. Based on the Lais of Marie de France, we propose to reread certain female relationships by taking seriously the marks of trust and love they show each other. Using two feminist concepts – sorority and the lesbian continuum – we will return to the lais of Milon, the Deux Amants and Eliduc. We aim to highlight the traits, mechanisms and functions of friendship between women in a fictional courtly context.